Long-range transport of atmospheric lead reaching Ny-Ålesund: Inter-annual and seasonal variations of potential source areas. (August 2016) - Bazzano, Andrea; Cappelletti, David; Udisti, Roberto; Grotti, Marco
Abstract: Atmospheric particulate matter (PM10 ) was collected at Ny-Ålesund (Svalbard Islands, Norwegian Arctic) during spring and summer from 2010 to 2014 and analysed for lead content, enrichment factor and isotopic composition ( 208 Pb/ 206 Pb and 207 Pb/ 206 Pb). It was found that atmospheric lead was mainly of anthropogenic origin and neither its mean concentration, nor its isotopic composition was subjected to significant inter-annual differences ( p -value > 0.1). Seasonal differences in both lead content and isotopic compositions occurred ( p -value < 0.001), with the exception of 2013 samples. Lead content in spring was higher than in summer. Isotopic analysis indicated that mining and smelting activities in the Rudny Altay region (Central Eurasia), as well as industrial emission in north-eastern North America, were the main sources of atmospheric lead in spring and summer, respectively. During 2013, no significant differences between the two seasons were found ( p -value > 0.3), showing a prolonged influence of Eurasian sources also in summer. The results obtained by the Pb isotopic composition were corroborated by a back-trajectory cluster analysis of air-masses reaching the sampling site. Graphical abstract: Highlights: Atmospheric lead reaching Ny-Ålesund is mainly anthropogenic. Lead concentration was higher in spring than in summer. Smelting activities in the Rudny Altay region were the main sources of atmospheric lead during spring. Industrial emission in North America accounted for most of atmospheric Pb in summer. During 2013 Eurasian inputs were predominant in both seasons.